Pengembangan Numerasi Siswa Tunarungu SLB Negeri Kandat Melalui LHT Kamus Bima (Bahasa Isyarat Matematika) - Santia, Ika; Handayani, Aprilia Dwi; Rochana, Siti; Prasetyani, Tamara Jasmine; Ilham, Slamet Muhammad; Mohammad, Nanda Nacaska Oktihsani (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2023)
Pedagogical Content Knowledge Technology (TPACK) is a framework that combines technology, teacher teaching skills, and knowledge. TPACK helps students learn numeration. However, the facts in the field show that students are still very short in numeration, especially the bullshit. This is demonstrated by the results of observations carried out in February 2023 at the Kandat State SLB, which showed that 77.8% of SD-LB 6th grade students have not yet been able to use the integer, and 85.7% of high school-level students have yet to use an integer multiplication. The results show that numeration needs special attention as it helps the student acquire the basic skills needed for life. This is the reason why the TPACK authorization should be given to the SLB teacher. This skill improvement can be achieved through the development of the Mathematical Sign Language (BIMA) learning product, which was developed using the ADDIE development model. The IHT results from the BIMA development show that students are better at counting.